FACTORS INFLUENCING TECHNOLOGY ADOPTION BY TRADITIONAL AFRICAN VEGETABLE FARMERS IN NORTHERN GHANA - Issaka, Y. B.; Nyarko, G.; Quaidoo, D. (UDS International Journal of Development, 2021)
The production of traditional African vegetables is an age-old tradition among the people of the northern region of Ghana. However, the knowledge base of traditional African vegetable production remains local due to a lack of research and policy support. Therefore, the adoption of improved technology among traditional vegetable farmers is generally low and impedes efforts to promote widespread cultivation, consumption and even commercialisation. This study aims at clarifying potential factors that determine the adoption of technologies by traditional African vegetable farmers in the northern region of Ghana. One hundred and five (105) respondents in five communities and across two administrative districts in the northern region were selected for an in-depth survey using a combination of quantitative and qualitative data collection methods. In addition, a logit regression was used to determine the effect of various factors on technology adoption by farmers. Among the factors, the educational level of a farmer, access to credit, farm size, experience in farming and access to extension support were found to be important factors affecting the decision of traditional African vegetable farmers to adopt improved technology. The results of this study can help enhance the effectiveness of policy re-orientation towards a more effective commercialisation of traditional African vegetables in Ghana and elsewhere.